1984
DOI: 10.1159/000260768
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Natural Plaque-Inhibiting Substances from ‘Nigerian Chewing Sticks’

Abstract: Aqueous extracts, 1% (w/v), of Nigerian chewing sticks derived from the African plants Serindeia warnecki, Prosopsis africana, Pseudocedrela kotschyi, and Anoigeissus schrimperi were found to effectively inhibit the attachment of S. mutans 6715wt13 to glass or saliva-coated hydroxy-apatite beads. It was shown that the active compounds in these extracts interfere with binding of the bacteria, resulting in reduced adherence. Although no large effect upon the total extracellular glucan synthesis was noted, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 9 publications
(12 reference statements)
2
75
1
2
Order By: Relevance
“…was beyond the scope of our study, a commonality of this genus is their relatively high levels of a number of tannin components including exifone (4-galloylpyrogallol), ellagic acid dehydrate, trimethyl ellagic acid, chebulic acid, corilagen, castalagin and chebulagic acid. 6,[8][9][10] Gallotannins have been reported to inhibit the growth of a broad spectrum of bacterial species 29 through a variety of mechanisms including binding cell surface molecules including lipoteichoic acid and proline-rich cell surface proteins, 30,31 and by inhibiting glucosyltransferase enzymes. 32 Ellagitannins have also been reported to exert antibacterial activity via several mechanisms including interaction with cytoplasmic oxidoreductases and by disrupting bacterial cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…was beyond the scope of our study, a commonality of this genus is their relatively high levels of a number of tannin components including exifone (4-galloylpyrogallol), ellagic acid dehydrate, trimethyl ellagic acid, chebulic acid, corilagen, castalagin and chebulagic acid. 6,[8][9][10] Gallotannins have been reported to inhibit the growth of a broad spectrum of bacterial species 29 through a variety of mechanisms including binding cell surface molecules including lipoteichoic acid and proline-rich cell surface proteins, 30,31 and by inhibiting glucosyltransferase enzymes. 32 Ellagitannins have also been reported to exert antibacterial activity via several mechanisms including interaction with cytoplasmic oxidoreductases and by disrupting bacterial cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported potent growth inhibitory activities for a number of tannin compounds. Gallotannins have been reported to inhibit the growth of a broad spectrum of bacterial species 45 through a variety of mechanisms including binding cell surface molecules including lipotoichoic acid and proline-rich cell surface proteins, 46,47 and by inhibiting glucosyltransferase enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…42 Furthermore, many tannin compounds have bacterial growth inhibitory activity. Gallotannins inhibit the growth of a broad spectrum of bacterial species 44 through a variety of mechanisms including binding cell surface molecules including lipotoichoic acid and proline-rich cell surface proteins, 45,46 and by inhibiting glucosyltransferase enzymes. 47 Elligitannins are also highly potent inhibitors of bacterial growth, with MIC values as low as 62.5 µg/ml.…”
Section: Discussionmentioning
confidence: 99%